The Mystery of the Missing Dog - Cynthia Rylant (New York, United States Scholastic US, 1995)
When an invisible dog "disappears" from a local show, the young sleuths from Invisible Inc. must employ the help of their invisible associate in order to solve the mystery. Original.
Keywords: Leveled Reader -- Leveled Reader